‘Every One of You Is a Leader’: Investigating the Experience of Being a Brown British Muslim Woman in Professional Contexts - Zaidi, Saiyyidah (Religions, 2024)
The Hadith paraphrased as ‘every one of you is a leader’ does not discriminate in gender in any way—both men and women are leaders. What does this mean in practice, and how are Muslim women perceived and received in line with this Hadith? Only in very recent years are Muslim women in Britain starting to occupy prominent positions: 13 Muslim women Members of British Parliament were elected in 2024; celebrities such as baker Nadia Hussain are regularly seen on British TV; and others such as Fatima Manji in the media. In this article, I explore how different ‘contextual intersectionalities’ influence and impact a Muslim woman and her leadership role. How does the intersectionality of her outward expression of faith identify her? How does a Muslim woman navigate a space where she is the leader and her skills are sought, yet her faith representation may instigate unconscious/conscious biases? Using an autoethnographic method, I investigate the impact of my identities as a Brown British Muslim woman in three distinct settings. First, in the professional and academic space of British Christian practical theology, where I was the first British Muslim to obtain a doctorate in the subject and was the first Muslim Trustee and Committee Member of the British and Irish Association for Practical Theology (BIAPT) between 2020 and 2024. Second, as a leadership advisor and executive coach to FTSE-listed companies, where I support C-suite leaders to generate sustained change in individuals, teams, and systems. And third, as a tutor and supervisor of proven business leaders to master the skills of coaching in their own right. I discuss how I am met in these spaces and the impact of that on my being. In conclusion, I call for increased understanding and awareness of the emotional tax paid by Muslim women who choose to take leadership roles.